TORSIONAL WAVE SCATTERING IN TWO-LAYER PIPE WITH ACCOUNT FOR CONTACT RIGIDITY - Konstantin E. Abbakumov; Nikolay V. Stepanenko (Известия высших учебных заведений России: Радиоэлектроника, 2018)
The purpose of the paper is to study the wave propagation in a two-layer pipe, taking into account the rigidity of the contact between its layers. It is considered by solving the equation of motion for the vector and scalar potentials. A dispersion equation describing the frequency distribution of the phase velocities of waves in the waveguide under investigation is derived. In order to take into account the degree of contact rigidity between layers additional terms are added to the boundary conditions, including the normal (kGN) and tangential (kGT) contact rigidity coefficients. It is shown that torsional waves are separated from other types of waves and can be considered separately. The example of a numerical solution of the dispersion equation shows the possible behavior of dispersion curves without regard to the contact rigidity. The similar problem solution is provided with allowance for contact rigidity at various perforation coefficients. A conclusion is drawn on the effect of contact between layers on torsional wave behavior. The similar method solves the problem for a homogeneous pipe with internal stratification. Recommendations are given for taking into account the revealed regularities in the development of ultrasonic methods of control based on torsional wave propagation.